2012
DOI: 10.7314/apjcp.2012.13.5.2369
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-center Survey of HPV Knowledge and Attitudes Toward HPV Vaccination among Women, Government Officials, and Medical Personnel in China

Abstract: Asian Pacific J Cancer Prev, 13, 2369-2378 IntroductionCervical cancer is the second most common cancer among women worldwide, with an estimated 529,000 new cases and 275,000 deaths occurring every year (Ferlay et al., 2010). Over 85% of the cases occur in developing countries like China, where it accounts for 13%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
54
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 19 publications
10
54
1
Order By: Relevance
“…Most studies focused on females' knowledge (Brisson and Edmunds, 2003;Insinga et al, 2004;Mahdavi and Monk, 2005;Dasbach et al, 2006;Eltoum and Roberson, 2007;Zhao et al, 2012) and do not include comparisons of knowledge among men and women. However, men play an important role in transmitting HPV and some studies reported the role of men as an important part of transmission and major groups needed more education about HPV (Wendell, Cohen et al 2003;Nash et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies focused on females' knowledge (Brisson and Edmunds, 2003;Insinga et al, 2004;Mahdavi and Monk, 2005;Dasbach et al, 2006;Eltoum and Roberson, 2007;Zhao et al, 2012) and do not include comparisons of knowledge among men and women. However, men play an important role in transmitting HPV and some studies reported the role of men as an important part of transmission and major groups needed more education about HPV (Wendell, Cohen et al 2003;Nash et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of Chinese women found misconceptions and knowledge deficits to be common regarding cervical cancer, HPV infection and HPV vaccination (Chan et al, 2007;Lee et al, 2007;Kwan et al, 2008;Li et al, 2012;Zhao et al, 2012;Choi et al, 2013). Most studies indicate a positive relationship between individuals' cancer-related risk perceptions and their attitudes, intentions, and actions regarding health protective and cancer preventive behaviors: if people consider cancer as controllable/preventable by their efforts they are more likely to seek medical care promptly, undergo cancer screening tests, or adopt healthy behaviors (Figueiras and Alves, 2007;Cameron, 2008;Sullivan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately more than 80% of HPV infections are removed over a 3-4 years without any intervention; on the other hand primary prevention trough vaccination and screening for cervical cancer seems to be effective (Wong, 2009). HPV vaccine is safe and reduces development of cervical cancer up to 70% (Medeiros, 2005;Zhao et al, 2012) which should be administered before or shortly after sexual contact to have optimal effectiveness (Markowitz et al, 2007;Pollack …”
Section: Introductionmentioning
confidence: 99%